Assessment of the interlaminar strength of resistance-welded PEI/carbon fibre composite - Reis, Jonas Frank [UNESP]; Abrahao, Ana Beatriz Moreira; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (Taylor & Francis, 2018)
This study has as its main objective to evaluate the effectiveness of the welding process by electrical resistance in a composite poly (ether-imide) matrix reinforced with continuous fibres of carbon, from the study of the thermal and mechanical properties of the welded joint. To evaluate the thermal properties of the welded material, samples were subjected to analysis by thermogravimetry and by thermomechanical analysis. With the intention to study the resulting weld interface, studies were made from the shear tests ILSS and Iosipescu, as well as end-notched flexure (ENF). The results of the thermal analysis in laminated non-welded PEI/carbon fibre show that the beginning of degradation for these composites is 460 °C, and it is also evident that the glass transition temperature of welded samples is about 15% higher than the results from samples not welded. The mechanical tests show that there was an increase of 32 and 20%, respectively, in interlaminar shear results for the ILSS- and Iosipescu-welded samples when they are compared to samples not welded. The ENF test results show satisfactory values of interlaminar fracture toughness in the composite welded from the values found in the literature.
Keywords: Composites; electrical resistance welding; mechanical test; thermal analyses